Maintaining Competitiveness Under Equilibrium Real Appreciation : The Case of Slovakia - Oomes, Nienke (IMF Working Papers; Working Paper ;, 2005)
This paper evaluates competitiveness in Slovakia and estimates the equilibrium real exchange rate for the koruna. Slovak wages and prices are found to have been relatively low even when adjusted for differences in relative income and productivity, suggesting an undervalued real exchange rate. However, recent rapid nominal appreciation has reduced most or all of this undervaluation and has brought the real exchange rate near or above equilibrium. The productivity-driven equilibrium real appreciation rate during 2005?09 is estimated at close to 3 percent per year but can be lower with the help of fiscal consolidation.